Innovation modes in the Swiss service sector: A cluster analysis based on firm-level data - Heinz Hollenstein (ETH Zurich, KOF Swiss Economic Institute, 2002)
The aim of this paper is, firstly, to contribute to the understanding of innovation patterns in services. To this end, firms which are similar in terms of a large set of innovation indicators were grouped into clusters. For the Swiss case, it was possible to identify five clusters which exhibit clearly different configurations of a large number of innovation-related factors (appropriability, etc.) and several structural properties of firms (size, etc.). The clusters may thus be interpreted as specific innovation modes. Secondly, we investigated whether these modes are economically equivalent. In such a case, the unordered classifying of similar firms would be more appropriate than the ranking of industries according to their innovativeness. The evidence supports the classification approach quite well; however, the ranking procedure cannot be completely refuted. Finally, this paper yields some insights into the differences between the innovation patterns prevailing in services and in manufacturing.
Keywords: 330; Innovation Patterns in Services; Knowledge Networks; Innovation Ranking vs. Classification; Non-technological Innovations; Dienstleistungssektor; Innovation; Clusteranalyse; Theorie; Schweiz